Reports on Workmen's Insurance in Germany (Quarterly Journal of Economics, 1887)
Reports on Workmen's Insurance in Germany Get access The Quarterly Journal of Economics, Volume 2, Issue 1, October 1887, Pages 66–67, https://doi.org/10.1093/qje/2.1.66 Published: 01 October 1887